An Evaluation of Muscle Repair Techniques: Implications in Musculoskeletal Healing and Corollaries in Oral-Facial Clefting - Jaehoon Kim (MDPI AG, 2021)
We performed an animal study to identify the techniques associated with the best muscle healing outcomes in cleft lip/palate surgery. The right triceps of thirty adult male Sprague–Dawley rats were cut and repaired by three different suture techniques: simple (n = 10), overlapping (n = 10), and splitting sutures (n = 10). Muscle tissues were isolated from 5 rats per group 1 and 8 weeks postoperation. The inflammatory response and muscle fiber healing were evaluated by hematoxylin and eosin (H&E) staining, Western blotting, immunohistochemistry for TNF-α and IL-1β, and immunofluorescence for laminin and MyoD. Grip strength (N/100 g) and spatial gait symmetry were evaluated before surgery and 1, 2, 4 and 8 weeks postoperation. Eight weeks postoperation, grip force per weight was significantly higher in the simple suture (median, 3.49; IQR, 3.28–3.66) and overlapping groups (median, 3.3; IQR, 3.17–3.47) than the splitting group (median, 2.91; IQR, 2.76–3.05). There was no significant difference in range of motion between groups. The simple group exhibited significant remission of inflammation by H&E staining and lower expression of TNF-α and IL-1β than the other groups by Western blotting and immunohistochemistry. Immunofluorescence revealed stronger expression of MyoD and weaker expression of laminin in the splitting group than in the other groups at week 8, indicating prolonged inflammation and healing followed by poor muscle fiber remodeling. Simple and overlapping sutures demonstrated similar functional healing, although greater inflammation and failure to maintain a thicker muscle belly were observed in the overlapping suture group compared with the simple suture group. Therefore, reconstruction of the philtral column with overlapping sutures alone may result in limited long-term fullness, and additional procedures may be needed.